From across the globe – traumatic injuries are an international concern at the US-Mexico border wall - Allison E Berndtson; Jay Doucet; Todd W Costantini; Laura Haines; Sarah Lagan; Laura Adams; Jarrett Santorelli; Gabriella Waters (Trauma Surgery & Acute Care Open, 2024)
Introduction Socio-economic and political events of recent years have caused a significant increase in immigrants attempting to illegally cross the United States (US)-Mexico border. While a 30-foot border wall separates the US and Mexico, immigrants from around the world have used this location as their point of entry to the US. These border crossings have led to a dramatic increase in major trauma resulting in increased inpatient resource utilization and the need for comprehensive hospital services. The aim of this study was to describe the nationality of injured immigrants admitted to a Trauma Center serving a segment of the US-Mexico border wall and to report their ultimate destinations after discharge.Methods We performed a retrospective review of patients admitted to an academic, Level 1 Trauma Center after injury at the US-Mexico border wall from 2021 to 2022. Demographic information was obtained from the trauma registry. The electronic medical record was searched to identify each patient’s self-reported country of origin. Patients’ nationality was then stratified by region of the world to understand geographic representation of border injury admissions.Results We identified 597 patients injured while crossing the US-Mexico border wall representing 38 different countries. The mean age of patients was 32.2±10.4 years and 446 (75%) were male. Most patients (405, 67.8%) were Mexican, followed by 23 (3.9%) patients from Peru, 17 (2.8%) patients from India, 14 (2.3%) patients from El Salvador, 13 (2.2%) patients from Cuba and 12 (2.0%) patients from Jamaica. When considering regions of the world other than Mexico, patients were most commonly from Africa, South America and Central America.Conclusion The increased volume of trauma associated with the US-Mexico border wall is a humanitarian and health crisis.(1) The diverse national origin of patients admitted after injury from border wall falls has shed new light on the social and interpreter services needed to care for these border injury patients and the challenges that exist in their post-discharge care.